Pemberdayaan Masyarakat Berbasis Potensi Lokal: Pendekatan Participatory Action dalam Penguatan Tata Kelola Desa - Novayanti Rukmana; Febrianto Syam; Muhammad Nur Yamin; Asri Nur Aina; Anna Fiulaizi (Arunika Media Nusantara, 2026)
Community empowerment grounded in local potential constitutes a strategic approach in strengthening rural governance. This article documents the role of a field supervisor lecturer (Dosen Pembimbing Lapangan/DPL) in facilitating a participatory action-based community service program through Kuliah Kerja Nyata (KKN) in Tabo-Tabo Village, Bungoro District, Pangkajene dan Kepulauan Regency, South Sulawesi. The DPL's supervisory functions encompassed needs identification, program planning facilitation, field coordination with village and sub-district governments, and reflective evaluation alongside students. Three program clusters directly aligned with the article's focus: (1) strengthening village governance through public information transparency and digital media development; (2) community economic empowerment through MSME legalization and local tourism asset development; and (3) social and infrastructure capacity building through environmental health activities and public facility revitalization. Results demonstrate that active DPL mentorship within a participatory framework effectively catalyzed multi-stakeholder collaboration, produced measurable community outcomes, and cultivated sustainable local capacity. These findings affirm that the DPL role extends beyond administrative supervision into substantive facilitation of community-based development grounded in local assets.